Mindfulness-based cognitive therapy: a promising new approach to preventing depressive relapse. - Williams, J; Kuyken, W (2012)
Mindfulness-based cognitive therapy (MBCT) was developed as a psychological approach for people at risk for depressive relapse who wish to learn how to stay well in the long-term. In this article we set out the rationale for MBCT, outline the treatment approach, overview the efficacy research to date and look to future challenges.